Design and Verification of a Blood Cell Separation Microfluidic Device - Gawanmeh, Amjad; AlAzzam, Anas; Mathew, Bobby (International Journal of Online and Biomedical Engineering (iJOE), 2017)
Blood cell separation microdevices are designed in biomedical engineering for the separation of particular cells from blood, such as cancer cells. The movement of blood microparticles, specially these cancer cells, in a continuous flow microfluidic device is controlled by several forces, as a result, understanding and guiding the movement of these microparticles is a challenging problem. These cells are subject to different types of forces that result from natural or external effects. These forces include gravity, and virtual mass, buoyancy, dielectrophoresis and, inertia force. Therefore, all of these are to be accounted for in any design or implementation of a system. This paper we use formal analysis of a separation microdevice in order to model and verify the the microparticle movement and behavior at high level of abstraction while considering different types of forces. The the dynamic behavior of the particle can be modeled as a Markovian decision process in order to predict the trajectory of microparticles. This model can be used to provide probabilistic analysis for the particle movement in the microdevice under the effect of different types of forces.